Dual Function for Mature Vascular Smooth Muscle Cells During Arteriovenous Fistula Remodeling. Issue 4 (April 2017) - Zhao, Jinjing; Jourd'heuil, Frances L.; Xue, Min; Conti, David; Lopez‐Soler, Reynold I.; Ginnan, Roman; Asif, Arif; Singer, Harold A.; Jourd'heuil, David; Long, Xiaochun
Abstract : Background: The arteriovenous fistula (AVF) is the preferred form of hemodialysis access for patients with chronic kidney disease. However, AVFs are associated with significant problems including high incidence of both early and late failures, usually attributed to inadequate venous arterialization and neointimal hyperplasia, respectively. Understanding the cellular basis of venous remodeling in the setting of AVF could provide targets for improving AVF patency rates. Methods and Results: A novel vascular smooth muscle cell (VSMC) lineage tracing reporter mouse, Myh11‐Cre/ERT2‐mTmG, was used to track mature VSMCs in a clinically relevant AVF mouse model created by a jugular vein branch end to carotid artery side anastomosis. Prior to AVF surgery, differentiated medial layer VSMCs were labeled with membrane green fluorescent protein (GFP) following tamoxifen induction. Four weeks after AVF surgery, we observed medial VSMC layer thickening in the middle region of the arterialized vein branch. This thickened medial VSMC layer was solely composed of differentiated VSMCs that were GFP+/MYH11+/Ki67−. Extensive neointimal hyperplasia occurred in the AVF region proximal to the anastomosis site. Dedifferentiated VSMCs (GFP+/MYH11−) were a major cellular component of the neointima. Examination of failed human AVF samples revealed that the processes of VSMC phenotypic modulation and intimal hyperplasia, as well as medial VSMC layer thickening, also occurred in human AVFs. Conclusions: We demonstrated a dual function for mature VSMCs in AVF remodeling, with differentiated VSMCs contributing to medial wall thickening towards venous maturation and dedifferentiated VSMCs contributing to neointimal hyperplasia. These results provide valuable insights into the mechanisms underlying venous adaptations during AVF remodeling.